Responsabilidade civil médica: dano estético e os efeitos produzidos pelo consentimento informado nos procedimentos e cirurgias plásticas estéticas - Bufarah, Mariana Havir (2024)
Given the significant increase in demand for aesthetic treatments in Brazil and around the world; the current majority understanding of doctrine and jurisprudence regarding the obligation assumed in surgeries of an exclusively aesthetic nature - considered as a result; the consequences - in terms of burden of proof - arising from the assumption of an obligation of result; the progressive horizontalization of the doctor-patient relationship; the broad recognition of the individual's self-determination; the evolution of research regarding personality rights; the growing recognition of the patient's consent as an act that legitimizes medical action and its correlation with the patient's life, psychophysical integrity and human dignity, this dissertation seeks to research the legal scenario surrounding the aforementioned topic - under the method of deductive approach and documentary procedure - observing, as a research technique, doctrinal, deontological and legislative collection and analysis, from the perspective of Comparative Law. This study demonstrates the relevance of transparency in the doctor-patient relationship, as well as the importance of objective good faith - from which the duty of information develops - and the legal and deontological value of informed consent, especially when considering aesthetic treatment